(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To study the current status of sleep quality in patients with advanced cancer treated at Thai Binh General Hospital in 2024. Methods: A cross-sectional descriptive study was conducted on 204 patients with advanced cancer being treated at the Oncology Center - Thai Binh General Hospital from July 2023 to July 2024. Patients’ sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Results: The average sleep time of patients was 4.59 ± 1.61; 21.6% of patients had very difficult sleep, 55.9% of patients had difficulty sleeping. In terms of the impact of sleep deprivation on daily activities, 12.3% of patients reported significant difficulties and 21.1% had mild difficulties. According to the Pittsburgh Sleep Quality Index (PSQI), only 6.4% of patients achieved good sleep quality, while 92.6% were classified as having poor sleep quality. Conclusion: The study results showed that most patients had poor sleep quality, and measures to improve sleep for patients were needed.